Compliance in Use of Self Protection Tools Case Study in Hospital Nurses in RSUD Ciamis, West Java - Nurtamimi, Fajrina; wati, Myrna; Salmah, Umi (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
The use of personal protective equipment is important for nurses to protect themselves from nosocomial infections in hospitals. The purpose of this study is to determine the level of nurse compliance in the use of personal protective equipment at patient unit of Ciamis Hospital, West Java. This study used a qualitative method with case study approach with two data types namely primary data and secondary data. Primary data with in-depth interviews and observation, secondary data from the review of documents and literatures. Compliance such as giving medical treatment to a patient showed that the nurse does not wear personal protective equipment in fit size. Nurses assumed that not all measures must use personal protective equipment. The results showed that nurses compliance in using personal protective equipment was still not proper.